Content and specificity of research activity of future teacher of philology: results of the experimental training - Artemenko, Olena (ScienceRise: Pedagogical Education, 2017)
The article is intended to identify psychological and pedagogical mechanisms of influence on productive research activity of the future teacher of philology in the context of personal approach. The priority and importance of research in the training of future teachers is emphasized. Proven to be one of the possible ways to radically change the situation in this area is a reorientation of the educational strategy of the higher school, its educational process on the radical changes in the training of teachers, where an important role is played by reorientation of the traditional system of organization of research work of students of pedagogical universities, its direction (organization) on the modification of existing professional values. It is accented by the fact that only dynamic change of yourself, your thinking makes possible self-formation and acquisition of the dynamic future teacher competence, providing professional success, innovation, forecasting changes and their originality, forms the mood for searching for the achievements and upholding truth, that is strong ethical sources that make up the moral foundations of the teaching profession